Effect of Alkanna tinctoria Root Against MRSA and MDR-Pseudomonas aeruginosa Biofilms on Excision Wound in Diabetic Mice: Comparative Study Between Methanolic Extract and Traditional Hydrophobic Preparation - Yasir Almuhanna; Mohammed Asad; Mohammed S. Alshammari; Babu Joseph (Biology)
Alkanna tinctoria, commonly called dyer’s alkanet (family-Boraginaceae), is used traditionally in Saudi Arabia to treat skin infections. A methanolic extract and a traditional formulation of the root used in folklore were prepared. LC-MS analysis was conducted to identify probable compounds present in the extract and the traditional hydrophobic formulation. The in vivo activity on excision wound was evaluated in diabetic mice while crystal violet assay was employed for in vitro evaluation. Human keratinocyte (HaCaT) cells were used to study in vitro cytotoxic effects. Several probable phytoconstituents were revealed by LC-MS analysis in the methanolic extract and the traditional formulation, and three of the constituents were the same. The extract ointment and traditional hydrophobic extract exhibited antibacterial and antibiofilm activity against both tested pathogens. The methanolic extract was relatively more cytotoxic on HaCaT cells compared to the hydrophobic formulation. The methanolic extract ointment did not significantly affect the wound healing, whereas the traditional formulation accelerated wound healing in diabetic mice. The results revealed that A. tinctoria in its traditional formulation is an effective wound healing agent but the methanolic extract of the plant does not affect the healing of wounds.